Anti-titin antibody is associated with more frequent hospitalization to manage thymoma-associated myasthenia gravis - Kim, Ki Hoon; Kim, Seung Woo; Cho, Jinhyuk; Chung, Hye Yoon; Shin, Ha Young (Frontiers in Neurology, 2022)
Background and purpose Anti-titin antibodies are antistriational antibodies associated with thymoma-associated myasthenia gravis (MG). We evaluated whether the patients with anti-titin antibody are more frequently hospitalized to manage thymoma-associated MG than those patients without anti-titin antibody. Methods Patients with thymoma-associated MG who conducted the serological test for anti-titin antibody were retrospectively included. Disease severity, treatments, MG-related annual hospitalization rate, and MG-related emergency room (ER) visit rate were compared between the patients with anti-titin antibody and those patients without anti-titin antibody. Multivariate analysis was conducted to analyze the association between anti-titin antibody serostatus and multiple admissions (hospitalization or ER visit of ≥2 times). Results Of the 64 included patients, 31 (48.4%) patients were positive for anti-titin antibody (titin+ group) and 33 (51.6%) patients were negative for anti-titin antibody (titin– group). Both the annual rate of MG-related hospitalization and ER visit were significantly higher in the titin+ group [0.2 (0.1–0.6) and 0.1 (0–0.2) per year, respectively] than those in the titin– group [0 (0–0.2) and 0 (0–0) per year, p = 0.004 and p = 0.006, respectively]. In multivariate analysis, positive anti-titin antibody was still significantly associated with multiple admissions [odds ratio (OR) 4.11, 95% CI 1.05–16.03] compared to the titin– group as a reference after adjusting for sex, follow-up duration, age at onset, systemic chemotherapy, and the Masaoka staging. Conclusion The presence of anti-titin antibody is associated with more frequent hospital utilization. Personalized explanation and careful monitoring strategy could be required in patients with thymoma-associated MG with anti-titin antibody for the timely detection of relapses.